Autologous hematopoietic stem cell transplant for the treatment of refractory myasthenia gravis with anti‐muscle specific kinase antibodies. Issue 2 (26th December 2022) - Beland, Benjamin; Hahn, Christopher; Jamani, Kareem; Chhibber, Sameer; White, Christopher; Atkins, Harold; Storek, Jan
Abstract: Introduction/Aims: Up to 25% of patients with myasthenia gravis (MG) have refractory disease despite trials of multiple immunosuppressants. Several case series describe acetylcholine receptor antibody‐positive (AChR) MG patients treated with autologous hematopoietic stem cell transplant (HSCT). In this report, we describe three patients with anti‐muscle‐specific kinase (MuSK) MG treated with HSCT. Methods: We included all patients who had undergone HSCT with anti‐MuSK myasthenia gravis identified through the records of the Alberta Blood and Marrow Transplant Program. We collected demographic and clinical data including validated MG scales as well as questionnaire data. Results: All 3 patients had severe disease (Myasthenia Gravis Foundation of America score IVb‐V) and were refractory to multiple treatments, including rituximab. All patients improved with no clinical manifestations or mild symptoms and remained as such for 2, 3.5, and 5.5 y. Adverse events ranged from treatable infections and transient dyspnea to persistent fatigue and premature menopause. The average worst Myasthenia Gravis Activities of Daily Living (MG‐ADL) scores improved from 14.7 before to 0.3 after HSCT. The mean worst Myasthenia Gravis Quality of Life Questionnaire (MG‐QoL15) scores improved from 26.7 to 0. All patients reported they would undergo transplant again for their MG. Discussion: We describe three patients with anti‐MuSK MG treated with HSCT, all of whom became symptom free from MG with a tolerable side effect profile. In patients with severe refractory anti‐MuSK MG, it may be reasonable to consider HSCT.